Arabic : A Linguistic Introduction - Ryding, Karin C. (Cambridge : Cambridge University Press, 2014)
This lively introduction to the linguistics of Arabic provides students with a concise overview of the language's structure and its various components: its phonology, morphology and syntax. Through exercises, discussion points and assignments built into every chapter, the book presents the Arabic language in vivid and engaging terms, encouraging students to grasp the complexity of its linguistic situation. It presents key linguistic concepts and theories related to Arabic in a coherent way, helping to build students' analytical and critical skills. Key features: Study questions, exercises, and discussion topics in every chapter encourage students to engage with the material and undertake specific assignments Suggestions for further reading in every chapter allow readers to engage in more extensive research on relevant topics Technical terminology is explained in a helpful glossary
Title from publisher's bibliographic system (viewed on 08 Oct 2015).